Readmission reasons of pediatric patients diagnosed with multisystem inflammatory syndrome after discharge - Ela Cem,; Elif Kıymet,; Elif Böncüoğlu,; Şahika Şahinkaya,; Miray Yılmaz Çelebi,; Mustafa Gülderen,; Aybüke Akaslan Kara,; Timur Meşe,; Hasan Ağin,; Nuri Bayram,; İlker Devrim, (Archives of Rheumatology, 2023)
Objectives: There is no clear information in the literature about causes of reactivation of multisystem inflammatory syndrome in children (MIS-C) or indications for readmissions for MIS-C after discharge; as a result, the conditions that may develop after infection in children with MIS-C were discussed, and the reasons for hospitalization were screened. Patients and methods: This single-center retrospective study was conducted with 95 patients (65 males, 30 females; mean age: 92.8±55.5 months; range, 5 to 17 months) between November 11, 2020, and December 30, 2021. Children who were rehospitalized in the study center after their discharge with the diagnosis of MIS-C were included in the study, and the indications for readmissions were evaluated. Results: During the study period, six (6.3%) patients (4 males, 2 females; median age: 114.5 months [interquartile range: 122 months]) had to be rehospitalized. Four of these patients had an underlying disease, while the other two were previously healthy children. Fever was the most common reason for readmissions in half of the patients, while the remaining patients were readmitted with the indications of myocarditis, pneumonia, and posttraumatic pain syndrome. Conclusion: Although no evidence for the reactivation of MIS-C was detected in patients in the literature, it should also be emphasized that close follow-up of these patients is a must, considering possible cardiac complications.